The pandemic: An epiphany of relations and opportunities for transcendence - Donati, Pierpaolo (Church, Communication and Culture, 2022)
The pandemic has caused social relations to emerge as the leading players in our lives. This translation of a chapter from the book Dopo la pandemia. Rigenerare la società con le relazioni [After the pandemic: Regenerating society with relations] explores the differences between interpersonal relations and role relations, showing the insufficiency of Modernity’s understanding of the social fabric. It describes the acceleration of digitalization and its consequences on social relations, assessing the long-term challenges and showing that it is necessary to build up a new culture of relations that make for a good life.